2011
DOI: 10.1089/thy.2010.0453
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Fibrous Thyroiditis (Riedel Thyroiditis): The Mayo Clinic Experience, 1976–2008

Abstract: IFT often is associated with a systemic extracervical fibrotic process and tobacco use. Attempted thyroid resection often results in postoperative complications. Long-term follow-up showed no deaths from IFT and showed stability of the thyroiditis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
115
1
14

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(137 citation statements)
references
References 42 publications
7
115
1
14
Order By: Relevance
“…A rare thyroid pathology clinically associated with an increased thyroid consistency is Riedel's thyroiditis (6). The sonoelastographic image of Riedel's thyroiditis in two patients has just been described, revealing heterogeneous stiffness of thyroid parenchyma ranging from 21 to 281 kPa (7).…”
Section: Discussionmentioning
confidence: 99%
“…A rare thyroid pathology clinically associated with an increased thyroid consistency is Riedel's thyroiditis (6). The sonoelastographic image of Riedel's thyroiditis in two patients has just been described, revealing heterogeneous stiffness of thyroid parenchyma ranging from 21 to 281 kPa (7).…”
Section: Discussionmentioning
confidence: 99%
“…The true incidence is unknown, but in a 1985 review of 56,700 thyroidectomies performed at Mayo Clinic, only 37 cases of Riedel's thyroiditis were identified. [6] Due to extensive fibrosis of the thyroid tissue along with surrounding soft tissue, it generally presents as a firm mass in the thyroid, with compressive symptoms . [5,7] Riedel's thyroiditis presents as a painless mass as is not preceded by acute inflammatory process.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies consider an immune disorder to be the most likely cause [3,5]. Recent research has shown that immunoglobulin G4-related systemic disease (IgG4-RSD) is likely involved [4,[6][7][8][9][10]. It is difficult for physicians to distinguish Riedel's thyroiditis from malignant neoplasms of the thyroid clinically because both clinical examination and imaging of Riedel's thyroiditis suggests malignancy [11].…”
Section: Discussionmentioning
confidence: 99%